Arylallenes and the halogeno-B(C6F5)2 reagents: facile formation of 2-borylindenes. Issue 68 (7th August 2019) - Tao, Xin; Daniliuc, Constantin G.; Soloviova, Kateryna; Strassert, Cristian A.; Kehr, Gerald; Erker, Gerhard
Abstract : Allenylarenes are converted to the respective 2-borylindenes by treatment with chloro- or bromobis(pentafluorophenyl)borane. Abstract : Phenylallene reacts rapidly with ClB(C6 F5 )2 to give the respective 2-borylindene. Several substituted allenylarenes form the respective 2-B(C6 F5 )2 boryl-substituted indenes upon treatment with ClB(C6 F5 )2 or BrB(C6 F5 )2 as well. Bis- and tris-allenylarenes form the corresponding products featuring multiple five-membered ring annulations, including a symmetrical tris-borylated dihydro-1 H -trindene derivative. The B(C6 F5 )2 borylindenes show fluorescence properties.